Pembelajaran Menanam Padi untuk Melatih Motorik Halus pada Anak Usia Dini - Septiani Hapidah; Aldila Andari Kristi; Dhian Riskiana Putri (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The research aims to develop fine motor skills in only childhood trought rice planting activities at the TA Sanggar Anak Alam (SALAM) located in Nitiprayan village, kasihan,bentul, a village located on the border of the Yogyakarta district and Bantul district. With a total of 29 students. Fine motor skills, namely this movements, will coordinate the eyes and hands in a fairly good movement control which allows them to carry out precision and precision in small muscle movements. Learning activities to plant rice for kindergarten aged children’s fine motor skills aim to hone children’s motor coordination skills.